Early in vitro development of daptomycin non-susceptibility in high-level aminoglycoside-resistant Enterococcus faecalis predicts the efficacy of the combination of high-dose daptomycin plus ampicillin in an in vivo model of experimental endocarditis. (14th February 2017) - Pericàs, J. M.; García-de-la-Mària, C.; Brunet, M.; Armero, Y.; García-González, J.; Casals, G.; Almela, M.; Quintana, E.; Falces, C.; Ninot, S.; Fuster, D.; Llopis, J.; et al.
Abstract : Background: Previous studies showed development of daptomycin non-susceptibility (DNS: MIC >4 mg/L) in Enterococcus faecalis infections. However, no studies have assessed the efficacy of the combination of daptomycin/ampicillin against E. faecalis strains developing DNS in the experimental endocarditis (EE) model. Objectives: To assess the in vitro and in vivo efficacy of daptomycin at 10 mg/kg/day, daptomycin/ampicillin and ampicillin/ceftriaxone against two high-level aminoglycoside-resistant E. faecalis strains, one developing DNS after in vitro exposure to daptomycin and another that did not (DS). Methods: Subculture of 82 E. faecalis strains from patients with endocarditis with daptomycin MICs, time–kill and in vivo experiments using the EE model. Results: 33% of the strains (27 of 82) displayed DNS after subculture with daptomycin. Daptomycin MIC rose from 0.5–2 to 8–16 mg/L. In time–kill experiments, when using a high inoculum (10 8 cfu/mL), daptomycin/ampicillin was synergistic for one-third of DS strains and none of DNS strains, while ampicillin/ceftriaxone retained synergy in all cases. In the EE model, daptomycin did not significantly reduce cfu/g from vegetations compared with control against either strain, while daptomycin/ampicillin reduced significantly more cfu/g than daptomycin against the DS strain, but not against the DNS strain [2.9 (2.0–4.1) versus 6.1 (4.5–8.0); P  =   0.002]. Ampicillin/ceftriaxone was synergistic and bactericidal against both strains, displaying the same activity as daptomycin/ampicillin against the DS strain. Conclusions: Performance of an Etest for daptomycin MIC after subculture with daptomycin inhibitory doses on strains of high-level aminoglycoside-resistant E. faecalis endocarditis may be an easy test to predict the in vivo efficacy of daptomycin/ampicillin.